Methane emission factor of open deposits used to store swine slurry in Southern Brazil - Sardá, Luana Goulart; Higarashi, Martha Mayumi; Nicoloso, Rodrigo da Silveira; Oliveira, Paulo Armando Victória de; Falkoski, Camila; Ribeiro, Stephanie Mayara Siega; Coldebella, Arlei (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to contribute to the establishment of a baseline for the methane emission factor for the management of swine manure, considering the current practice of raw manure storage in two open deposits in parallel, in Southern Brazil. Methane (CH4) emissions were continuously measured in three PVC tanks of 3 m3, during 180 days, in the summer. As the content of volatile solids of pig slurry ran out in approximately 130 days, the CH4 emission factor was calculated as B0= 0.48 m3 kg-1 VS. Although this value is higher than the B0 estimated by Intergovernmental Panel on Climate Change for Latin America (0.29 m3 kg-1 VS), it is in agreement with the B0 estimated for developed countries (0.45 and 0.48 m3 kg-1 VS, for the US and EU, respectively). The graphic of accumulated CH4-C emission x time fitted a sigmoidal, kinetic model (r2= 0.998) that showed a good correlation when tested with the emission data collected from a slurry deposit, under field conditions, in winter. This suggests that the model reproduces the CH4 emission kinetics in the region. By applying the reviewed state law rules (retention time of 50 instead of 120 days), estimates by the sigmoidal equation show that it is possible to reduce in more than 80% methane gas emission.